Strategi Total Quality Management (Tqm) Terhadap Peningkatan Mutu Pendidikan SMP Bani Saleh 2 - Haratua, Chandra Sagul; Jumriah, Mina Arafah; Santriyani, Eny; Widita, Istri Candra; Lesmana, Galang Surya (Jurnal Ilmiah Wahana Pendidikan, 2022)
The main problem with Indonesian education today is the low quality of education, whereas to maintain the quality of education, quality control is needed to monitor the process and all school supporting components. TQM (Total Quality Management) is a management approach for an organization that is centered on quality and relies on the participation of all its members. TQM aims for long-term success through customer satisfaction and benefits to all members of the organization and society as a whole. The aim of this research is to determine and assess the role of the principal, the role of teachers, and the role of administration in improving the quality of education at Bani Saleh 2 Middle School. This school is a junior high school in Bekasi City, West Java. This school has achieved many achievements in the non-academic field, namely Tapak Suci pencak silat. In this research, we used qualitative methods involving interviews and a one-day field survey. The results of our observations and interviews with the Principal, Teachers and Administrators of Bani Saleh 2 Middle School show that all the workers there have good quality competencies in carrying out their respective job responsibilities. Students at Bani Saleh 2 Middle School have shown that this school has quality seen through its teachers and educational staff. The quality of teachers and educational personnel will produce students who have various kinds of achievements. Most of the achievements at this school come from non-academic fields, so this makes students more motivated to continue their enthusiasm for achieving achievements in the academic field..